Flow Experience and Team Performance: The Role of Team Goal Commitment and Information Exchange - Caroline Aubé; Éric Brunelle; Vincent Rousseau (Motivation and Emotion, 2014)
While a number of studies show that the flow experience is related to different outcomes at the individual level, the role of flow in work teams remains unclear. This study contributes to the advancement of knowledge on flow by testing the relationships between this psychological state, team goal commitment and team performance. Data were gathered from 85 teams comprised of graduate and undergraduate students who participated in a project management simulation. The results show that the flow experience is positively related to team performance. This relationship is mediated by team goal commitment and moderated by the level of information exchange between team members. In practical terms, the results of this study show that managers should implement interventions fostering the flow experience in their teams, while at the same time encouraging information exchange between members.
Keywords: 330; flow experience; team performance; goals commitment; information exchange